Biophilic Design: Virtual Nature Application in a Windowless Room - Wilda Maulina; Dalhar Susanto (Sinektika: Jurnal Arsitektur, 2023)
Biophilic design recommends the connection between humans and nature because it positively influences human health and well-being. Due to the pandemic, some humans have been forced to work at home or in windowless rooms. This situation makes occupants unable to connect with nature. One solution in biophilic design is to present natural substitute elements such as virtual nature to reconnect nature in spaces that cannot access it. This paper discusses the application of virtual nature in windowless space which aims to help users get positive benefits for affective well-being (AWB) such as emotions and moods. This paper is compiled through literature exploration by synthesizing various previous research results. Based on several studies, shows that virtual nature is not just replacing real nature but is a boundary of the interior that reconnects with nature. This connection emotionally determines the quality of the windowless room so that it has benefits for the well-being of the occupants, especially affective well-being (emotions and moods).